Efeitos do pré-condicionamento isquêmico no desempenho de atletas de Taekwondo - Cristiano Arruda Gomes Flôr (2021)
Ischemic preconditioning (IPC) can be defined as applications of brief periods of ischemia followed by periods of reperfusion. The literature presents indications that this technique increases the performance in several physical capacities, an has as possible explanations some physiological mechanisms such as a lower rate of ATP depletion with an energy saving effect on muscle work, less accumulation of blood lactate and reduced muscle glycogen depletion. Due to the similarity between the types of abilities that are influenced by IPC and the physical demands of taekwondo, it is possible to hypothesize that the IPC can improve the physical performance of taekwondo athletes, although no works were found in the literature. Thus, the aim of the present work was to verify the effects of ischemic preconditioning on the performance of taekwondo athletes. Two studies were carried out. In Study 1, eleven national/international level athletes underwent a IPC or placebo (PLA) procedure in both lower limbs, consisting of 4x5 minutes of occlusion, interspersed with 5 minutes of reperfusion, at an individualized occlusion pressure in the IPC situation and standardized in the PLA situation. Before the IPC/PLA procedures, the countermovement jump (CMJ) were performed. Then, the volunteers performed the CMJ before and after and the specific aerobic test for taekwondo (TET) after IPC or placebo procedures, performed randomly. Heart rate (HR) was continuously monitored during the test, the subjective rating of perceived exertion (RPE) was recorded at the end of the test. In summary, the results of study 1 did not verify significant differences in performance on the TET, given by the time to exhaustion (PLA: 960.2±97.4 seconds; IPC: 989.1±77.7 seconds; p= 0.375; d=0.328; ES: small) and neither in the HR responses (PLA: 194±10 bpm; IPC: 195±8 bpm. p=0.955; d=0.010; ES: trivial) and RPE (PLA: 9.6±0.7 au; IPC: 9.6±0.7 au; p=1; d=0; ES: small). Still, in the CMJ there was no main effect of the moment (p=0.908; ηp2 =0.00027; ES: trivial), the condition (p=0.625; ηp2 =0.00038; ES: trivial) or the interaction between moment and condition (p=0.921; ηp2=0.00025; ES: trivial). In Study 2, fourteen national/international level athletes were submitted to the same treatments as in Study 1 (randomized IPC or placebo). Then, the volunteers perform 3 blocks of a battery of tests that consisted of CMJ and 3 repetitions of a specific anaerobic test for taekwondo (FSKTmult), with a 1-minute interval between each test. Rest time between each test block was 30 minutes. Heart rate (HR) was continuously monitored during the tests, the subjective perception of exertion (RPE) was recorded at the end of each one of the blocks. The results of study 2 did not verify significant differences in FSKTmult performance, given by the total number of kicks per condition (PLA: 828±72 kicks; IPC: 832±62 kicks; p=0.686; d= 0.011; ES: trivial) and by the number of kicks per block in each situation, with no main effect of the moment (p=0.667; ηp2 =0.031; ES: small), of the condition (p=0.686; ηp2 =0.013; ES: small ) or the interaction between moment and condition (p=0.896; ηp2 =0.008; ES: trivial). There was also no effect for the CMJ in relation to the condition (p=0.731; ηp2 =0.009; ES: trivial), the moment (p=0.414; ηp2 =0.058; ES: moderate) or the interaction between moment and condition (p =0.749; ηp2 =0.022; ES: small); and for RPE of the condition (p=0.423), of the moment (p=0.806) or of the interaction between moment and condition (p=0.620). For HR, an effect was found on the moment (p=0.0004; ηp2 =0.453; ES: large), but not on the condition (p=0.924; ηp2 =0.0001; ES: trivial) or on the interaction between moment and condition ( p=0.057; ηp2 =0.198; ES: large). The combined results of this thesis showed that the bilateral lower limb IPC procedure did not change the performance of taekwondo athletes in specific tests of the modality, as well as the performance in the CMJ, suggesting that this procedure, in the configuration that was adopted, was not beneficial. for the performance of taekwondo athletes.